Optimization of discrete structure of electrospark coatings - V. Antonyuk; L. Lopata (Проблеми трибології)
The presented article considers the disadvantages of chromium coatings and shows the possibility of their elimination by obtaining coatings of discrete structure. The principle of coatings of discrete structure allows to organically combine physical processes underlying pulse hardening methods with a discrete structure determining their service properties. It is shown and substantiated that the method of electric spark alloying is the most suitable for applying discrete coatings, since this process is discrete by its nature. The advantage of discrete coatings is the absence of a softening effect when a brittle crack passes from the coating to the base metal due to excessively high adhesive strength. High cohesive and adhesive resistance of individual discrete sections of the coating is achieved by limiting normal stresses in the coating and tangential stresses in the plane of adhesive contact with the base by changing the size and shape of an individual section. This article is devoted to determining the optimal parameters of a discrete structure. The required coating design is determined by a calculation method based on a model that describes the stress-strain state of the coating.